Effect of fluxes on weld penetration during TIG welding – A review. (2023) - Rakesh, N.; Mohan, Ajay; Navaf, P.; Harisankar, M.S.; Nambiar, Sreehari J.; Harikrishnan, M.; Devadathan, J.S.; Rameshkumar, K.
Abstract: Tungsten Inert Gas (TIG) welding, also known as Gas Tungsten Arc Welding (GTAW), is a common welding procedure which produce high quality weld with composition as close to that of parent metal. Wide range of materials like, ferrous alloys, magnesium alloys, Aluminum alloys and Titanium alloys can be welded using TIG welding process. Conventional TIG welding can only produce a maximum penetration of 3 mm in a single pass. Alloys with higher thickness require multi-pass TIG welding which involves preparation of joint and additional filler. This leads to the increase in production cost and higher heat input which leads to increased thermal stress and distortion of weld. This paper reviews recent novel developments to improve the penetration depth in TIG welding of various materials. The application of Activated Flux induced TIG welding (A-TIG), Flux Bounded TIG welding (FBTIG) and Flux cored wire TIG of A-TIG on Ferrous alloys, Titanium alloys, Magnesium alloys and Aluminum alloys are discussed. The paper also discusses about the mechanism involved in improving the penetration of weld in these three processes. It also discusses the future scope of application of these processes.